Supplementum 272: Abstracts of the Annual meeting of the Swiss Society of Gastroenterology, the Swiss Society of Visceral Surgery, the Swiss Association for the Study of the Liver and the Swiss Society of Endoscopy Nurses and Associates - Swiss Society of Gastroenterology; Swiss Society of Visceral Surgery; Swiss Association for the Study of the Liver; Swiss Society of Endoscopy Nurses and Associates (Swiss Medical Weekly, 2023)
No abstract available.